(untitled) (Global Journal of Science Frontier Research, 2017)
There have been discourses on the issues of health care differences between the developing and developed world and the need to bridge the health care divide or the provision of health care services for all countries. A case study between Haiti and Harvard highlighted the poor and good state of health care system as it relates to causes of death. Though, universal health care is high and unsustainable as a result of several militating factors including cost and politics, cost is not as important as saving a life, recognizing human rights, resources for economic productivity, lowering the cost of health care, which implies that every hand must be on deck including the government, individuals, organizations and other richer countries to help develop a good health care system. Hence, the debate of sustainability health care system or universal health care is based on the matter of social, political and economic sustainability and policymaking.